Clinical Subtypes of Frontotemporal Dementia. (November 2015) - Ghosh, Sayantani; Lippa, Carol F.
Frontotemporal dementia (FTD) was one of the lesser known dementias until the recent advancements revealing its genetic and pathological foundation. This common neurodegenerative disorder has three clinical subtypes- behavioral, semantic and progressive non fluent aphasia. The behavioral variant mostly exhibits personality changes, while the other two encompass various language deficits. This review discusses the basic pathology, genetics, clinical and histological presentation and the diagnosis of the 3 subtypes. It also deliberates the different therapeutic modalities currently available for frontotemporal dementia and the challenges faced by the caregivers. Lastly it explores the scope of further research into the diagnosis and management of FTD.